THE EFFECT OF USING WEBTOON COMICS IN READING COMPREHENSION OF SEVENTH-GRADE STUDENTS AT SMPN 3 BANYUWANGI IN THE ACADEMIC YEAR 2023/2024 - Wulan Elok Wahyu Lestari; Nur Hasibin; Inayah, Arin; Abdul Halim (LUNAR, 2025)
The purpose of this research was to find out whether using Webtoon Comics has an effect on reading comprehension of procedure text. This research used a quantitative research method with a one-group pre-test and post-test pre-experimental research design. The respondents were 34 students in seventh grade. The researcher gave the students a pre-test before giving the treatment, and the post-test was given after the students received treatment from the researcher. In this research, the data was collected by giving a test. The T-test analysis formula was used in this research to determine the difference between the average of the post-test and the pre-test in the experimental class. The T-test was analyzed and interpreted with the degree of signification level was 5% with df = 33, and the t-table was 2.034. The result of the T-test analysis was 10.092. It means that the T-test (10.092) was higher than the t-table (2.034) in the significance of 5%. Based on the research results, it can be concluded that the use of Webtoon Comics as learning media was effective for learning reading comprehension